PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Via Nur Kharomah (Politeknik Negeri Semarang, 2022)
This study aims to find out how the variables of Firm Size, Leverage, and Profitability affect Earning Management in Mining Industry companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sample data used were 17 mining industry companies. The method of data analysis was carried out by the method of multiple linear regression analysis with the help of the SPSS version 22.0 application. The results of this study indicate that firm size has a significant negative effect on earnings management, leverage has an insignificant negative effect on earnings management, and profitability has a significant positive effect on earnings management.